PREDICTION OF UNFAVORABLE COURSE OF NEPHROTIC SYNDROME IN CHILDREN: THE MULTIMARKER PARALLEL CASCADE SYSTEM - Fomina, S. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of study was to investigate the possibility of using the results of different diagnostic tests in children with nephrotic syndrome (NS) asprognostic markers during disease course. Materials and methods. The operating characteristics of values derived in dynamic renoscintigraphy and indirect renangiography with 99mTc-DTPA, static renoscintigraphy with 99mTc-phosphate, levels of urine renospecific enzymes (N-acethyl–D-glucosaminidase and -galactosidase) were estimated in 480NS children depending on disease activity. Results. Different levels of prognostic valuefor studiedparameters were confirmed depend ofNS outcome. Conclusion. Renoscintigraphy indexes and urine renospecific enzymes activity levels should be used as markers of the progression in NS children with the glance to optimal terms of studies’ conduction and range parameters. The multimarker parallel cascade Systemfor prediction of unfavorable NS course has been initiated. This System can be regarded as the start ofa new strategic goalfordetermination ofrelevant unfavorable disease courseparameters in any branch ofmedicine.